The Role of The Village Financial System (Siskeudes) in Mediating The Relationship Between The Role of Village Apparatus and The Competency of Village Apparatus Towards Accountability for Village Fund Management - Ningsih, Winda; Anggraeni, Windi Ariesti (Fakultas Ekonomi Universitas Garut, 2023)
The aim of this research is to examine the role of the village financial system in mediating the influence of the role of village officials and the competence of village officials on the accountability of village fund management. This research took place in the context of number-based research using direct information obtained from surveys of respondents. This research used a sample of 30 villages and 90 questionnaires which were distributed to respondents including village heads, village secretaries and village financial leaders. Then the data was analyzed by applying the Partial Least Square (PLS) approach with the Structural Equation Modeling (SEM) model. The findings in this research state that the involvement of village officials, the capacity of village officials, and the village financial system (siskeudes) have a significant impact on accountability in managing village funds. Then siskeudes is also partially able to mediate the interaction between the role of village officials and the competence of village officials towards accountability in managing village funds.